MODEL OF ENVIRONMENT FOR INTERNET BASED SYSTEMS FUNCTIONING - Globa, Larysa; Kot, Tetiana (International Journal of Computing, 2010)
Internet based information systems (IBIS), their functioning and design features are presented in this paper. The requirements to IBIS information-computation processes are specified and IBIS architecture is proposed. The model of the IBIS functioning environment, document and business-process models are presented.